Preserving Local Values in Indonesia: Muslim Student, Moderate Religious, and Local Wisdom - Maghfur Ahmad; Siti Mumun Muniroh; Umi Mahmudah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
This study aims to determine the impact of Muslim student religiosity on local wisdom in Indonesia. This studyuses a quantitative approach by distributing questionnaires to 1026 students. The sample is taken based on thepurposive sampling technique, which is only targeting Muslim students who practice moderate Islamic teachings.This study uses five dimensions of religiosity, namely spirituality (X1), ideological (X2), intellectual (X3),experiential (X4), and consequential (X5). To estimate the effect of these dimensions, this study applies multiplelinear regression models. The results reveal there is a positive relationship between students’ religiosity and localwisdom in Indonesia. Empirical evidence also indicates that there are only three dimensions of religiosity that havea positive and statistically significant effect on local wisdom, namely ideological, intellectual, and consequential.Then, the consequential dimension has the highest effect, where the regression coefficient is 1.54. Meanwhile, thedimensions of spirituality and experience are known to have a positive but insignificant effect. The implication isthat Muslim students who have an open attitude and are not rigid are very good social assets in preserving thevalues of local wisdom in Indonesia.